Pengaruh Profitability, Liquidity, Size, Growth, Dan Capital Structure Terhadap Nilai Perusahaan - Riska, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study discusses to analyze and analyze the effect of profitability, liquidity, company size, company growth and capital structure on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The purposive method used in determining samples with several criteria was obtained by 74 samples of manufacturing companies and using linear multiple regression analysis. The results showed that profitability, liquidity, company size and company growth had no significant effect on firm value while capital structure had a positive and significant effect on firm value.